2021
DOI: 10.1152/jn.00577.2020
|View full text |Cite
|
Sign up to set email alerts
|

The roles of lower- and higher-order surface statistics in tactile texture perception

Abstract: Humans can haptically discriminate surface textures when there is a significant difference in the statistics of the surface profile. Previous studies on tactile texture discrimination have emphasized the perceptual effects of lower-order statistical features such as carving depth, inter-ridge distance, and anisotropy, which can be characterized by local amplitude spectra or spatial-frequency/orientation subband histograms. However, the real-world surfaces we encounter in everyday life also differ in the higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…An area for future research could involve combining sets of similar or more complex stimuli with visual cues. While Yamada’s study demonstrated that random dots could be easily discriminated visually, it is known that humans struggle to identify regular patterns in more complex stimuli or high-order statistics, as observed by Fujii et al ( Fujii et al, 2003 ) and in Kuroki et al’s research ( Kuroki et al, 2021 ), respectively. This difficulty may be attributed to the nature of the task, which involves discriminating regularity rather than randomness.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…An area for future research could involve combining sets of similar or more complex stimuli with visual cues. While Yamada’s study demonstrated that random dots could be easily discriminated visually, it is known that humans struggle to identify regular patterns in more complex stimuli or high-order statistics, as observed by Fujii et al ( Fujii et al, 2003 ) and in Kuroki et al’s research ( Kuroki et al, 2021 ), respectively. This difficulty may be attributed to the nature of the task, which involves discriminating regularity rather than randomness.…”
Section: Discussionmentioning
confidence: 95%
“…However, not all studies on tactile texture perception have used simple geometric patterns. In a study exploring the perception of surface statistics, Kuroki et al ( Kuroki et al, 2021 ) found that while human perception in other modalities, like vision, can utilize both lower- and higher-order image statistics, the tactile system primarily relies on lower-order statistics for texture discrimination, even when presented with surfaces transcribed from natural scenes. In our current work, while we maintain consistent dot properties, the spatial arrangement and perceived randomness of these dots vary.…”
mentioning
confidence: 99%
“…We believe that the sensory pathways in sound and touch are yet to be explored, and more studies are needed using controlled textural stimuli. Recent advances in algorithms to create textures, along with advances in 3D printed and organic haptics technologies, can produce textures with specific textural properties (Heeger & Bergen, 1995; Kuroki et al, 2021; Metzger et al, 2021; Sahli et al, 2020; Tymms et al, 2018). Further experiments with these artificially created textures can unearth feature-based interaction between textures from different modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Different groups of 15 participants took part in Experiments 2a, 2b, and 2c, Experiments 1d and 1e, and Experiments 2d and 2e. The number of participants was predetermined to be comparable to previous studies [11,23,[26][27][28] in which tactile perception was tested by stimulating the fingertips with similar stimuli. There were partial overlaps of participants across experiments.…”
Section: A Participantsmentioning
confidence: 99%
“…The tactile system has multiple mechanoreceptor-afferent channels that differ in their frequency sensitivity profiles [6][7][8]: SA1 channels are most sensitive to slow indentation of the skin i.e., low-frequency vibrations (< 10Hz), RA channels exhibit sensitivity to middle-range vibration, and PC channels show high sensitivity at around 250 Hz. Indeed, previous studies have repeatedly shown the high performance of human participants in discriminating vibration frequencies, as well as discriminating textures based on temporal differences in skin deformation [8][9][10][11][12][13][14]. Human observers also have a high sensitivity to the orientation and motion direction of the input [15][16][17][18].…”
Section: Introductionmentioning
confidence: 98%